Home Language Environment and Executive Functions in Mexican American and Chinese American Preschoolers in Head Start. Issue 4 (19th May 2022) - Haft, Stephanie L.; Gys, Christopher L.; Bunge, Silvia; Uchikoshi, Yuuko; Zhou, Qing
ABSTRACT: Rerch Findings : Using two groups of dual language learners (DLLs), the current study examined links between two developmental constructs closely linked to school readiness: the home language environment (HLE) and executive function (EF). In a sample of 90 children (age range = 38–70 months, 59% girls) from either Mexican American (MA, N = 46) or Chinese American (CA, N = 44) low-income families enrolled in Head Start preschool programs, parents reported on their HLE (home language balance, home English/heritage language activities) and children's EF (inhibitory control and attention shifting) was measured by cognitive tasks. Findings showed preschool-aged DLLs in low-income immigrant families received more heritage language exposure relative to English language exposure at home. Several demographic variables (parental education, per capita income, DLL group, child age of English acquisition, child generation, child English receptive vocabulary) were related to various aspects of HLE. Controlling for covariates, the amount of heritage language activities at home was uniquely and positively related to children's attention shifting. Pe or Policy : The findings underscore the importance of incorporating language background considerations when designing intervention programs that target HLE and EF in low-income DLLs.